Oil spill monitoring in north sea and bohai sea using high resolution X-band sar imagery - Velotto, Domenico; Lehner, Susanne (European Space Agency (Special Publication) ESA SP, 2013)
Offshore crude oil production has grown regularly since its beginning in the early 1940s, it accounts today for almost one-third of the world's production. This growth goes along with the production plateau reached in the last decades by onshore installations. As a direct consequence also the sea oil pollution caused by operational offshore activities has increased. In this paper results of oil spill monitoring using X-band SAR imagery are shown. North Sea and Bohai Sea are two hot spots because they are reach of oil fields.
CRIS-Team Scopus Importer:2024-03-18